The impact of oral direct thrombin inhibitors on activated clotting time during catheter ablation in patients with atrial fibrillation. (24th May 2021) - Mine, T; Kitagaki, R; Fukuhara, E; Ishihara, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Direct thrombin inhibitors (DTIs) unlike factor Xa-inhibitors (Xa-inhibitors) is associated with fewer bleeding complications than warfarin in patients who had catheter ablation (CA) for atrial fibrillation (AF). However, the mechanisms remains unclear, and activated clotting time (ACT) is used to control heparin-dose for thromboembolic prevention during CA. Methods: We retrospectively studied 543 patients taking direct oral anticoagulant (DOAC) who underwent CA for AF (375 males, age 67 ± 10, 251 non-paroxysmal AF, 142 DTIs). Patients with off-label usage of DOAC were excluded. ACT was measured before (Pre-ACT) and after (post-ACT) initial heparin administration (3000U + 100U/kg), and total heparin-dose was evaluated. Results: Pre-ACT and post-ACT were extended in patients with DTIs (150 ± 21 vs 123 ± 15; P < 0.0001 and 322 ± 39 vs 309 ± 42 sec; P = 0.0013). Patients with Xa-inhibitors required higher total heparin-dose (199 ± 43 vs 175 ± 34 U/kg; P < 0.0001). During and after CA, none had thromboembolic events and 14 patients (3 DTIs, 11 Xa-inhibitor) showed bleeding events (Figure). Conclusions: ACT is extended in patients taking DTIs. Xa-inhibitors might have anticoagulant effects which are not reflected in ACT.